Jawabanmu

2014-03-22T11:53:26+07:00
A. 32 + 4x -  x^{2} = 0
= (-x-4) (x-8)
 x = -4 / x = 8

b. 4 x^{2} - 16x + 15 = 0
= (2x - 5) (2x - 3)
x =  \frac{5}{2}   /  x =  \frac{3}{2}
  
A. 32 + 4x - x^2 = 32 + 8x - 4x - x^2 = (32 + 8x) - (4x + x^2) = 8(4 + x) - x(4 + x) = (8 - x) (4 + x)
B. 4x^2 - 16x + 15 = 4x^2 - 10x - 6x + 15 = (4x^2 - 10x) - (6x -15) = 2x(2x - 5) - 3(2x - 5) = (2x - 3) (2x - 5)
2014-03-22T11:53:57+07:00
a. 32 + 4x - x² = 0
(x+8)(x-4)

(x+8) = 0 /(x-4)= 0
x=-8          x=4
hs= {-8,4}